Androgen receptor expression inversely correlates with immune cell infiltration in human epidermal growth factor receptor 2–positive breast cancer. (November 2018) - van Rooijen, Johan M.; Qiu, Si-Qi; Timmer-Bosscha, Hetty; van der Vegt, Bert; Boers, James E.; Schröder, Carolien P.; de Vries, Elisabeth G.E.
Abstract: Introduction: Although targeting human epidermal growth factor receptor 2 (HER2) is a meaningful treatment in HER2-positive breast cancer, ultimately resistance develops. Androgen receptor (AR) expression and immune cell infiltration are thought to be involved in trastuzumab response and may, therefore, be of interest as additional targets for therapy in HER2-positive breast cancer. Aim: To improve insights into the presence among AR expression, immune cell infiltration and HER2, we analysed HER2-positive breast tumours. Methods: Primary tumours of 221 patients treated with trastuzumab for metastatic disease were selected. HER2 status was centrally confirmed. AR, T-cells (CD3 and CD8), programmed cell death protein 1 (PD-1) and PD-1 ligand 1 immunohistochemical staining and M2 tumour-associated macrophages (TAMs; CD68 and CD163) immunofluorescence were performed. Tumour-infiltrating lymphocytes were evaluated by haematoxylin and eosin staining. Results: Sufficient tumour material was available for 150 patients. Oestrogen receptor was expressed in 51.3% of the tumours and AR in 81.3% of the tumours. AR expression was inversely correlated with M2 TAM ( Pearson's r  = −0.361, P  < 0.001), CD3+ ( r  = −0.199, P  < 0.030) and CD8+ ( r  = −0.212, P  < 0.021) T-cell infiltration. Clustering analysis showed high immune cell infiltration in AR low-expressing tumours, and low immune cell infiltration in AR-high expressing tumours. Conclusion: AR expression inversely correlates with immune cell infiltration in HER2-positive breast cancer. Highlights: Androgen receptor (AR) expression was studied in human epidermal growth factor receptor 2–positive advanced breast cancer. AR expression was negatively correlated with immune cell infiltration. The strongest negative correlation with immune cell infiltration was with M2 tumour-associated macrophages. A subgroup was identified with low immune cell infiltration and high AR expression.